If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+5-3x-7=2x+5(-3x+6-8)
We move all terms to the left:
4x+5-3x-7-(2x+5(-3x+6-8))=0
We add all the numbers together, and all the variables
4x-3x-(2x+5(-3x-2))+5-7=0
We add all the numbers together, and all the variables
x-(2x+5(-3x-2))-2=0
We calculate terms in parentheses: -(2x+5(-3x-2)), so:We get rid of parentheses
2x+5(-3x-2)
We multiply parentheses
2x-15x-10
We add all the numbers together, and all the variables
-13x-10
Back to the equation:
-(-13x-10)
x+13x+10-2=0
We add all the numbers together, and all the variables
14x+8=0
We move all terms containing x to the left, all other terms to the right
14x=-8
x=-8/14
x=-4/7
| 5-3g+7g=3+5g | | -4n=-4(8n+6)-4 | | 4x+10=-6x-70 | | 3x-50=1/5x+20 | | -18x-3x=105 | | 5r=8.6 | | 2x+6=-1-8 | | -1/2e=9 | | F(-5)=4/3x-5 | | 1.8j-3.47=-6.02+3.9j-2.4j | | 8x−16=4x−56 | | 10x-32=88 | | 3x+1+2x+2=48 | | 9(3x+5)−18=5(2x+6)+31 | | 6x+7+2x-11=180 | | 5x-2x+7=21 | | 3x+2/7=5x-4 | | 116=6x-2 | | 3^(6x+5)=5^(2x-1) | | q - 12 = 1 | | 2(w-2)-6=-2(-8w+6)-6w | | 2x=(x+9)+60 | | 2x+1+90=6x-9 | | 6.5n-10=4.4n+6 | | 4=x5-1 | | (8a)(5a-2)=180 | | 7+3u=-3+4u | | 7x-8+3(3x+2)=-2(x+9) | | 2x+14=6x+6 | | 4/5(0.5x-3/4)=-1/2 | | -8+2x=3x-1 | | 0.4(b+2)=4 |